Perubahan-Perubahan Segmental pada Pertumbuhan Anak Perempuan Umur 7-10 Tahun di Yogyakarta - Adi Soekarto Adi Soekarto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
The growth in stature actually consists of segmental growth, because it could be divided into various segments, i. e.: head and neck, trunk, and upper and lower leg. All segments grow independently under their own velocity; the stature is the same as the sum of the length of all segments. The body width also grows at about equal'speed as the trunk.Four samples of girls, between seven to ten years of age, are taken from the collected data in the Department of Physical Anthropology, Gadjah Mada University Faculty of Medicine. The increment of body length is mainly caused by leg length between seven to eight and nine co ten years of age, and by the trunk length between eight to nine years of age.Key Words: segmental growth - stature - Indonesian children - trunk length - leg length